Journal of Pharmaceutical Health Care and Sciences - Sai, Yoshimichi
Journal of Pharmaceutical Health Care and Sciences (JPHCS) is an open access, peer-reviewed journal that encompasses clinical pharmacy as well as clinical and experimental pharmacotherapy. JPHCS welcomes Research articles, Review articles (invitation only), Case reports and Short communications. Topical areas of interest include: Outcome research on pharmacotherapy and pharmaceutical health care Rational and appropriate pharmacotherapy in relation to clinical and/or experimental indices Clinical pharmacy Pharmacoepidemiology Pharmacoeconomics Drug informatics Pharmacy services research Medication management Other aspects of pharmaceutical health care and sciences JPHCS is the official publication of the Japanese Society of Pharmaceutical Health Care and Sciences.